2016
DOI: 10.1186/s12876-016-0523-3
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-five years of advocacy for patients with gastroparesis: support group therapy and patient reported outcome tool development

Abstract: BackgroundGastroparesis (Gp) is a poorly understood chronic gastrointestinal medical condition for which patient reported outcomes (PRO) are lacking. Previously developed symptoms scoring has been used for several decades. Using symptoms scores as a basis for documentation, 12 years of support/focus group patient feedback from the nearly 1000 attendees were integrated with medical care and recommendations for treatment were developed. Early attenders of the support group were compared with non-attendees for il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…In our study population, one of five patients with positive GAD‐65 antibody had diabetic Gp while rest (80%) had idiopathic Gp. This is different from a study by Dhamija et al who reported 22% frequency of GAD antibody positivity in idiopathic achalasia patients compared to 2.3% among 171 controlled age‐matched subjects with only one patient with GAD positivity had DM …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study population, one of five patients with positive GAD‐65 antibody had diabetic Gp while rest (80%) had idiopathic Gp. This is different from a study by Dhamija et al who reported 22% frequency of GAD antibody positivity in idiopathic achalasia patients compared to 2.3% among 171 controlled age‐matched subjects with only one patient with GAD positivity had DM …”
Section: Discussionmentioning
confidence: 99%
“…This is different from a study by Dhamija et al 39 who reported 22% frequency of GAD antibody positivity in idiopathic achalasia patients compared to 2.3% among 171 controlled age-matched subjects with only one patient with GAD positivity had DM. 24,39 Histological evidences of gastric enteropathies in Gp patients are not extensive but have now been defined. Recent advances in the field of GI motility disorders have generated considerable attention toward autonomic enteropathies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Baseline patient‐reported symptom scores were recorded using a standardized questionnaire during a clinic visit prior to temporary stimulator placement. Illness severity scores (IDIOMS) were calculated using a composite of clinician‐determined illness severity, number of organ systems involved, and the intensity of services utilized, similar to the factors used in Medicare DRGs . Four‐hour gastric emptying times (via scintigraphy) and resting cutaneous EGG also were recorded prior to temporary GES placement.…”
Section: Methodsmentioning
confidence: 99%